1989
DOI: 10.1111/j.1476-5381.1989.tb11858.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT2 receptors in the behaviours produced by intrathecal administration of selected 5‐HT agonists and the TRH analogue (CG 3509) to rats

Abstract: 1 The behavioural effects of the intrathecal injection of a thyrotrophin-releasing hormone (TRH) analogue L-orotyl-L-histidyl-prolineamide (CG 3509, 0.5 /g), the non-selective 5-HT, and 5-HT2 receptor agonist 5-methoxy-N,N'-dimethyltryptamine (5-MeODMT, 2-100pg) and the selective 5-HT2 receptor agonist 2,5-dimethoxy-a,4-dimethyl-benzene ethamine hydrochloride (DOM, 2-25 ug) were compared with the response of systemically administered 5-MeODMT (2 mg kg-1, i.p.) in rats, to establish whether the agonist-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Most importantly, selective 5-HT 2A antagonists block the HTR induced by DOI and other hallucinogens (Schreiber et al, 1995; Fantegrossi et al, 2005, 2006, 2008, 2010), and hallucinogens do not induce the HTR in 5-HT 2A knockout mice (Gonzalez-Maeso et al, 2003, 2007; Keiser et al, 2009; Halberstadt et al, 2011). Although phencyclidine (Nabeshima et al, 1987), benzodiazepines (Tadano et al, 2001), the CB 1 antagonist SR 14176A (Darmani and Pandya, 2000), the 5-HT 1A antagonist WAY-100635 (Darmani, 1998), and thyrotropin-releasing hormone analogs (Fone et al, 1989) induce the HTR, these effects are blocked by 5-HT 2A receptor antagonists. Because of this specificity, this behavior has been widely adopted as an animal behavioral assay for 5-HT 2A activation and hallucinogen-like effects.…”
mentioning
confidence: 99%
“…Most importantly, selective 5-HT 2A antagonists block the HTR induced by DOI and other hallucinogens (Schreiber et al, 1995; Fantegrossi et al, 2005, 2006, 2008, 2010), and hallucinogens do not induce the HTR in 5-HT 2A knockout mice (Gonzalez-Maeso et al, 2003, 2007; Keiser et al, 2009; Halberstadt et al, 2011). Although phencyclidine (Nabeshima et al, 1987), benzodiazepines (Tadano et al, 2001), the CB 1 antagonist SR 14176A (Darmani and Pandya, 2000), the 5-HT 1A antagonist WAY-100635 (Darmani, 1998), and thyrotropin-releasing hormone analogs (Fone et al, 1989) induce the HTR, these effects are blocked by 5-HT 2A receptor antagonists. Because of this specificity, this behavior has been widely adopted as an animal behavioral assay for 5-HT 2A activation and hallucinogen-like effects.…”
mentioning
confidence: 99%
“…Immediately following injection of DOI or saline, subjects were placed into a Plexiglas testing bin (60 cmr45 cmr 45 cm) lined with Aspen chip bedding. During a 30-min interval in the testing bin, they were scored for the occurrence of wet-dog shakes (defined as a paroxysmal shudder of the head, neck and trunk ; Bedard and Pycock, 1977 ; and back muscle contractions (defined as a clear-cut powerful contraction sweeping from the back of the neck along the back to the tail ; Fone et al, 1989).…”
Section: Behavioural and Thermal Testing Proceduresmentioning
confidence: 99%
“…The m echanism underlying T R H augm entation of dopam ine-dependent behaviours is still u n d er dis cussion. A p art from th e conflicting reports concerning the ability of T R H to enhance the release of dopam ine (Miyamoto et al, 1981;Sharp et al, 1982;Xu et al, 1990;M éndez et al, 1993), it is also able to inhibit the uptake of dopam ine (Prasad, 1987(Prasad, , 1991 277 (1995) [63][64][65][66][67][68][69] these properties may underlie the ability of T R H to alter dopam ine-dependent effects, it cannot underlie the wet-dog shakes th at are elicited by TR H , since 5-H T2a receptors appear to be involved in this T R H effect (Fone et al, 1989a), Today, there are several T R H analogues th a t are known to produce T R H effects. Previously, we have shown that the T R H analogue, A^a-[{(5)-4-oxo-2-azetidinyI}-carbonyI]-L-histidyl-L-proIinamide dihydrate (YM-14673), elicits dopamine-like behaviours such as sniffing and hyperlocomotion (Yamamoto et al, 1990).…”
Section: Introductionmentioning
confidence: 99%